Coping and resilience as predictors of adolescent self-harm - Van der Wal, Wilmie (University of the Free State, 2017)
Self-harm by adolescents is manifesting as one of the contemporary global mental health problems as incident rates are increasing worldwide. This self-harming trend is increasingly becoming a concern to South African adolescents who seemingly have adopted many practices of the Western World. Given the growing pains of transformation and high violence and crimes rates affecting the youth of the South African democracy, adolescents are being challenged continuously to cope with these circumstances. The aim of the study was to investigate whether coping and resilience can predict adolescent self-harm in the Free State Province in South Africa. A non-experimental, cross-sectional, correlational design was used in this study. A stratified randomised sample of 962 learners from nine schools in the Free State Province was selected. The measuring instruments included a biographical questionnaire, from which the criterion variable was measured in a single closed-ended question, the Coping Schemas Inventory – Revised, and the Resiliency Scale for Children and Adolescents. A logistic regression analysis method was used to investigate the extent to which coping and resilience can predict self-harming behaviour. Results indicate a prevalence rate of self-harm of 17.35% among respondents. Females were more likely than males were to engage in self-harm (19.4% and 14.5% respectively); thus, gender significantly predicted self-harm (p = 0.025). Tension-reduction coping (p = 0.029) and emotional reactivity (resilience: p = 0.000) predicted membership to the self-harming group(s), whereas social support coping protects adolescents from self-harm (p = 0.017). Collectively, these variables explained 11.2% of the variance in self-harming behaviour. Given the limited research on self-harm in South Africa, it is suggested that further mixed-methods design approaches and longitudinal research be done with a cohort representative of South African adolescents to explore self-harm in the South African context in more detail.

Selfleed deur adolessente manifesteer as een van die kontemporêre geestesgesondheids-probleme in die wêreld soos wat voorkomssyfer wêreldwyd toeneem. Hierdie neiging tot selfleed word toenemend ŉ bekommernis vir Suid-Afrikaanse adolessente wat skynbaar baie praktyke van die Westerse Wêreld aangeneem het. Gegewe die groeipyne van transformasie en hoë koerse van geweld en misdaad wat die jeug van die Suid-Afrikaanse demokrasie affekteer, word adolessente voortdurend uitgedaag om hierdie omstandighede te hanteer. Die doel van die studie was om te ondersoek of hantering (“coping”) en veerkragtigheid (“resilience”) selfleed deur adolessente in die Vrystaat Provinsie in Suid-Afrika kan voorspel. ŉ Nie-eksperimentele, deursnee-, korrelasionele ontwerp is in hierdie studie gebruik. ŉ Gestratifiseerde, ewekansige steekproef van 962 leerders van nege skole in die Vrystaat Provinsie is geselekteer. Die meetinstrumente het ŉ biografiese vraelys, waaruit die kriteriumveranderlike in ŉ enkele geslote vraag gemeet is, die Coping Schemas Inventory- Revised, en die Resiliency Scale for Children and Adolescents ingesluit. ŉ Logistiese regressie-ontledingsmetode is gebruik om te ondersoek tot watter mate hantering (“coping”) en veerkragtigheid (“resilience”) selfleedgedrag kan voorspel. Resultate toon ŉ voorkomssyfer van selfleed van 17.35% onder respondente. Vroue het meer waarskynlik as mans by selfleed betrokke geraak (19.4% en 14.5% onderskeidelik); geslag voorspel dus selfleed beduidend (p = 0.025). Spanningvermindering-hantering (p = 0.029) en emosionele reaktiwiteit (veerkragtigheid: p = 0.000) het lidmaatskap van die selfleedgroep(e) voorspel, terwyl hantering (“coping”) deur middel van sosiale ondersteuning adolessente teen selfleed beskerm het (p = 0.017). Gesamentlik het hierdie veranderlikes 11.2% van die variansie in selfleedgedrag verklaar. Gegewe die beperkte navorsing oor selfleed in Suid-Afrika, word voorgestel dat verdere gemengdemetodeontwerp-benaderings gevolg word en longitudinale navorsing met ŉ verteenwoordige groep Suid-Afrikaanse adolessente gedoen word om selfleed in meer besonderhede in die Suid-Afrikaanse konteks te verken.
Dissertation (M.A. (Psyschology))--University of the Free State, 2017
Keywords: Coping; Self-harm; Resilience; Tension-reduction coping; Social support coping; Emotional reactivity; Self-mutilation in adolescence; Self-destructive behavior in adolescence; Teenagers -- Mental health